Anti-TNF Agents Restrict Adherent-invasive Escherichia coli Replication Within Macrophages Through Modulation of Chitinase 3-like 1 in Patients with Crohn's Disease. (12th January 2022) - Douadi, Clara; Vazeille, Emilie; Chambon, Christophe; Hébraud, Michel; Fargeas, Margot; Dodel, Marie; Coban, Dilek; Pereira, Bruno; Birer, Aurélien; Sauvanet, Pierre; Buisson, Anthony; Barnich, Nicolas
Abstract: Background and Aims: The mechanism of action of anti-tumour necrosis factor [anti-TNF] agents could implicate macrophage modulation in Crohn's disease [CD]. As CD macrophages are defective in controlling CD-associated adherent-invasive Escherichia coli [AIEC], anti-TNF agents could limit AIEC replication within macrophages. We assessed the effect of anti-TNF agents on AIEC survival within monocyte-derived macrophages [MDMs] from CD patients and attempted to identify the proteins involved. Methods: Peripheral blood MDMs were obtained from 44 CD patients [22 with and 22 without anti-TNF agents]. MDMs were infected with reference strain AIEC-LF82. Proteomic analysis was performed before and 6 h after AIEC-LF82 infection. Results: AIEC-LF82 survival was lower in MDMs from CD patients receiving anti-TNF agents compared to those who did not [−73%, p = 0.006]. After AIEC-LF82 infection, the levels of CD82 [ p = 0.007], ILF3 [Interleukin enhancer-binding factor 3; p = 0.001], FLOT-1 [Flotillin-1; p = 0.007] and CHI3L1 [Chitinase 3-like 1; p = 0.035] proteins were different within CD-MDMs depending on anti-TNF exposure. FLOT-1 [ϱ = −0.44; p = 0.038] and CHI3L1 [ϱ = 0.57, p = 0.006] levels were inversely and positively correlated with AIEC survival within MDMs from CD patients with or without anti-TNF, respectively. We observed a dose-dependent decrease of AIEC-LF82 survival after adjunction of anti-TNF within MDMs, inducing an increase of FLOT-1 and decrease of CHI3L1 mRNA levels. Neutralization of intra-macrophagic CHI3L1 protein using anti-CHI3L1 antibodies reduced AIEC survival within macrophages 6 h after infection [ p < 0.05]. Conclusion: Anti-TNF agents are able to restrict replication of pathobionts, such as AIEC, within macrophages by modulating FLOT-1 and CHI3L1 expression in CD patients.